Chipped or Whole? Listening to Survivors’ Experiences With Disclosure Following Sexual Violence - Scoglio, Arielle A. J. (Journal of interpersonal violence, 2022)
Sexual violence is a prevalent crime but vastly underreported and with serious long-term health consequences for survivors. Disclosure of sexual violence represents a social experience that may offer support towards healing or further traumatization depending on the response received. Although current research suggests that process of disclosure itself is important, as are social responses, there is a dearth of research examining the perceived impact of initial responses to disclosure on healing and relationships, particularly over time. The current study used data from nine focus groups with 45 survivors to explore the impact of initial disclosure reactions on recovery, from the survivors? perspectives. Constant comparative analysis identified several themes, including subtypes of positive and negative responses to disclosure and long-term impacts on healing and relationships. Survivors disclosed to informal and formal support persons and although many identified responses as positive or negative, some also experienced mixed responses. Survivors identified perceived long-term impacts on healing, interpersonal relationships, and social justice. Our findings suggest disclosures are a critical point for potential intervention after sexual violence. It is through the disclosure process that survivors can be supported and empowered to connect with others and move further along in their journey towards healing and recovery. Public awareness and promotion of positive responses could be designed to reach children and youth, so that the next generation is equipped with the tools to support each other in difficult times, particularly in the aftermath of sexual violence.